سنتِ نبوی ﷺ اور انسانی نفسیات: برصغیر کی صوفیانہ فکر کے تناظر میں ایک تجزیاتی مطالعہ - Dr Sabah Naz (Seerat Studies, 2025)
This article explores the intersection of Prophetic biography and human psychology, focusing on how the Sunnah offers comprehensive guidance for emotional balance, mental well-being, and behavioral refinement. The analysis engages with Qur’anic principles and Prophetic traditions that address psychological challenges such as distress, despair, and inner conflict, while emphasizing practices that nurture resilience, hope, and spiritual tranquility. Central to the discussion are the Prophet’s teachings on empathy, patience, compassion, and moral discipline, which serve as timeless models for psychological care. In addition, the intellectual and spiritual contributions of South Asian Sufi scholars are examined, as their writings and practices illuminate the ways in which the Prophetic model has been interpreted and applied to foster spiritual growth, emotional healing, and ethical transformation within diverse social contexts. By integrating the Prophetic tradition with Sufi thought, the study frames an interdisciplinary perspective that situates Islamic teachings as a resource for understanding and addressing human psychology. This approach not only enriches the discourse on the psychological dimensions of the Sunnah but also highlights its relevance to contemporary discussions on mental health, spirituality, and holistic well-being.